Influence of weather accelerated ageing on healing temperature sensitivity of asphalts. (25th January 2021) - Sun, Guoqiang; Ma, Jianmin; Sun, Daquan; Yu, Fan
Abstract: Healing characteristics of asphalt lay a foundation for the wide applications of permanent roads. However, the decay pattern of asphalt healing ability in actual climate environments still remains unclear. Hence, the weather accelerated ageing (WAA) influence on the healing temperature sensitivity of several representative asphalts is systematically investigated in this paper. Results from fatigue-healing-fatigue (FHF) experiment show that the WAA and terminal blend crumb rubber (TBCR) modification impart pronounced impacts to the healing temperature sensitivity of asphalts. Notably, it is found that the aged asphalt has a healing inertia zone with low healing temperature sensitivity, in which the healing ability of asphalt is at a relatively low level. Furthermore, four kinds of various index temperatures are put forward as the evaluation indicators to quantitatively characterize the influence of WAA on the healing temperature sensitivity, i.e. inert extended temperature at healing rate curve, inert extended temperature at healing percentage curve, top healing temperature (THT) shift value and complete healing temperature range (CHTR) shift value. Moreover, the greater the WAA resistance of asphalt, the smaller the WAA influence on its healing temperature sensitivity. The WAA reduces the differences of healing temperature sensitivity among various asphalts. Lastly, the thermal stability and phase behavior investigations reveal that the molecular compositions and phase state transition (PST) of asphalt will be changed after WAA, eventually inducing the healing temperature shift and the appearance of healing inertia zone. Graphical abstract: Image 1 Highlights: Four index temperatures are proposed to evaluate the influence of weather accelerated ageing (WAA). Terminal blend rubber modification impart pronounced influence on healing temperature sensitivity of asphalt. Weather accelerated aged asphalt has an obvious healing inertia zone with very low healing temperature sensitivity. The greater the WAA resistance of asphalt, the smaller the WAA influence on healing temperature sensitivity. WAA reduces the differences of healing temperature sensitivity among various asphalts.